An energy concerving modification of numerical methods for the integration of equations of motion. (1987) - Labudde, Robert A.; Greenspan, Donald
Abstract : In the integration of the equations of motion of a system of particles, conventional numerical methods generate an error in the total energy of the same order as the truncation error. A simple modification of these methods is described, which results in exact conservation of the energy.